Jual Beli Pakaian Bekas Dalam Perspektif Fikih Al-Bi’ah - Hidayah, Okti Nur Hidayah; Abdurrahman, M. Iqbal (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2024)
The textile industry has become a strategic sector in Indonesia, but it also ranks as the world's second-largest contributor to pollution. In the current fashion world, there is a trend known as thrifting, which involves buying and selling secondhand clothing. Through the sale of secondhand clothes, no waste is generated from the production of new garments. Islam, as the majority religion embraced by the Indonesian population, has a conceptual framework for addressing environmental issues known as Fikih al-biah. This research will delve into the buying and selling of secondhand clothing from the perspective of Fikih al-bi'ah. The study employs a library research methodology, utilizing secondary data from existing literature, which will be analyzed through the lens of Fikih al-bi'ah. The findings of this research indicate that engaging in the buying and selling of secondhand clothing, commonly referred to as thrifting, from the perspective of Fikih al-biah, or environmental conservation, can contribute to five main aspects of Islamic legal objectives: safeguarding religion, preserving life, protecting lineage, maintaining intellect, and upholding wealth.